Pelatihan dan Penerapan Manajemen SDM untuk Meningkatkan Produktivitas UMKM Berbasis Komunitas di Desa Padang Cermin, Kabupaten Pesawaran - Yudhinanto, Cahyo Nugroho; Zuhri, Khozainuz; Pramono, Doni Eko Hendro; Purnomo, Rosyana Fitria; Sari, Resy Anggun; Ikhwan, Ahmad; Hartanto, M Budi (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This community service activity aims to improve the productivity of community-based Micro, Small, and Medium Enterprises (MSMEs) in Padang Cermin Village, Pesawaran Regency through training and the application of human resource management (HRM) principles. The program was implemented using a participatory approach that included workshops, mentoring, and evaluation sessions. The training focused on HR planning, motivation, performance appraisal, and team collaboration to strengthen the internal capacity of MSME actors. The results showed that after the training and mentoring process, participants demonstrated a better understanding of HR management concepts and were able to apply them to their daily business operations. The productivity of MSME members increased, as reflected in improved time management, teamwork, and output quality. The conclusion of this activity indicates that the application of HRM practices can significantly enhance the efficiency and sustainability of community-based MSMEs.